2008
DOI: 10.1002/adem.200800241
|View full text |Cite
|
Sign up to set email alerts
|

Porous Metals and Metallic Foams: Current Status and Recent Developments

Abstract: Porous metals and metallic foams are presently the focus of very active research and development activities. There are currently around 150 institutions working on metallic foams worldwide, most of them focussing on their manufacture and characterisation. Various companies are developing and producing these materials which are now being used in numerous industrial applications such as lightweight structures, biomedical implants, filters, electrodes, catalysts, and heat exchangers. This review summarizes recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
300
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 736 publications
(309 citation statements)
references
References 83 publications
0
300
0
9
Order By: Relevance
“…The use of the metal mesh reinforced panels reduced the weight of the floors by 75% in comparison to conventional reinforced concrete decks [12]. Lefebvren et al [13], Banhart and Seeliger [11] and Smith et al [1] provide an extensive overview of current industrial applications of metallic foams.…”
mentioning
confidence: 99%
“…The use of the metal mesh reinforced panels reduced the weight of the floors by 75% in comparison to conventional reinforced concrete decks [12]. Lefebvren et al [13], Banhart and Seeliger [11] and Smith et al [1] provide an extensive overview of current industrial applications of metallic foams.…”
mentioning
confidence: 99%
“…Metal foams are made up of mesh pore and have a polyhedral shape exhibiting high specific surface area, low density, and large pore size, and have been widely used as catalyst support materials [27]. Roy et al developed a methane reforming reactor for hydrogen production with a Pd-Rh metal foam catalyst structure; they found that it demonstrated excellent catalyst stability and activity, and could be widely applied in the processing of solid oxide fuel cell [18].…”
Section: Introductionmentioning
confidence: 99%
“…For a review of the various core topologies and manufacturing methods employed in the creation of periodic cellular structures the reader is referred to Wadley [24] and Lefebvre et al [25]. Many of these studies fielded the cellular material in a sandwich panel configuration whereby the deflection of the face sheets can be used as a metric for measuring energy absorption.…”
Section: Introductionmentioning
confidence: 99%